EPISTHEMOLOGICAL STUDY OF TERATAI METHOD: New Offer on Arabic Language Teaching Methodology for Beginner- Intermediate Learner in Indonesia - Naifah, Naifah (VISION, 2014)
Abstract Â  Even in our modern schools, it is not unusual to Dnd teach- ers whose practice is shaped primarily from their past experiences. In the traditional language teaching methods, teachers offer course materials in a classroom where students listen, take notes, copy ma- terials, execute homework and complete assignments. In many cases lecturers fail to transfer knowledge to students effectively despite personally having sound technical knowledge in the subject area. However, the challenge that faces the education environment has always been to ensure that the teaching and learning process takes place effectively in a classroom environment. This paper focuses on the author s experiences in implementing an active method in Ara- bic language teaching to promote effective student learning. It ex- plores speciDc pedagogical theories combined with school resources to improve the quality of teaching and student learning. A simpli- Ded educational method for improving the quality of the teaching and learning process is presented. The method called âTeratai Â sug- gested that the effectiveness of the teaching and learning process is depend on the effective facilitation of communication, involvement and interaction among students, teachers and course content. The article is intended to explore episthemological consepts, assump- tions, approaches, constructions, and applications of Teratai method Â  in Arabic language teaching. The purpose of this discussion is to build the awareness of a variety of effective teaching ideas and tech- niques that a lecturer may consider in light of their current teaching styles and personalities. Â  Â  Key words: Teratai Method, language learning methodology, epis- themological study